Male Contraception - Amory, John K. (Seminars in Reproductive Medicine, 2023)
Approximately 40 to 50% of pregnancies are unintended. Contraceptive use significantly reduces the risk of unintended pregnancy. Approximately 70% of couples' contraceptive use is female and 30% is male, attributable to the reliance on condoms and vasectomies. Unfortunately, many women cannot use currently available contraceptives due to medical contraindications or side effects. At the same time, men want additional safe and effective contraceptive methods. Because of this, work to develop novel, safe, and effective male contraceptives is underway. This review will briefly discuss the pros and cons of condoms and vasectomies, and then describe research into the development of novel methods of male contraception, by the mechanism of action of the contraceptive. First, we will discuss male contraceptives that block sperm transmission. Next, we will discuss male contraceptives that impair sperm production. Lastly, we will discuss male contraceptives that impair sperm function.
Keywords: male contraception; spermatozoa; condoms; vasectomy; unintended pregnancy